Statistical Analysis of Customer Relationship Management (CRM), factors driving long term relationship, benefits, and customer centric holistic approach – A study (International Journal of Food and Nutritional Sciences, 2022)
The stellar purpose of the present study is to know how far the demographics of respondents impress on the study of CRM in commercial banks and to study the factors driving the long term relationship between banks and customers, to know the benefits of CRM and to know how CRM has become a customer centric holistic approach. The study highlights the significance of CRM and the factors impressing the CRM and how it has become the need of the day. Now-a-days CRM is acquiring more attention than previously as it is gaining popularity in retaining the customers and acquiring new customer. CRM involves using technology to organise, automatic and synchronise sales, marketing customer service and technical support (Robert Shaw, 1999). CRM is powerful strategy of Banking Industry enabling them to face severe competition, to survive and to explore new markets. It is proved all over the globe that the banking customers are demanding more and more products innovative in nature in order to satisfy their innovative needs.